PENGARUH CITRA MEREK DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK LUWAK WHITE KOFFIE PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN TERNATE - Darmin, Fardin; Fahri, Johan; Abubakar, Karim (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2021)
Objective: The purpose of this study was to determine the effect of Brand Image and Halal Labels both partially and simultaneously on the decision to purchase Luwak White coffee products. The analytical model used to test the hypothesis is multiple linear regression analysis, and the research method used is explanatory research with a quantitative approach and a sample of 50 respondents. Methodology: The analytical method used and Data processing techniques use SPSS 16 for windows.Finding: All hypothesis accepted at the 5% confidence level.Conclusion: The research proves that: first Brand Image has a positive and significant influence on Purchasing Decisions, which means that the better the perception and consumer confidence in the brand image of a product, will determine the purchasing decision of Luwak White Koffie Products. The second Halal Label has a positive and significant influence on purchasing decisions, which means that with the inclusion of halal labels on product packaging, it will directly affect consumers to make purchasing decisions Luwak White Koffie Products. With the results simultaneously both variables have a positive and significant effect on Purchasing Decisions.